QUESTIONING PKPU REPEATEDLY IN THE MIDST OF THE RAMPANT PKPU APPLICATION AS AN ALTERNATIVE TO DEBTOR DEBT SETTLEMENT - Nurhabsari, Irdinta Nurhabsari (LPPM, Universitas Muhammadiyah Riau, 2024)
Law No. 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (